The Power of Ignorance and The Roaring Girl. (12th September 2013) - Paul, Ryan Singh
Abstract : This essay explores the ways in which power employs ignorance in the construction of manageable subjects. Framing The Roaring Girl in epistemological terms, I suggest that Moll exceeds cultural categories of knowledge and makes visible what had previously and necessarily been ignored. She reveals that categories of social identity are produced as much by enforced ignorance as by regimented knowledge. Her transgressions of propriety and cultural expectations reveal that the cultural deployment of power‐knowledge is arbitrary and unstable, based on negative control and exclusion as much as on codified traditions of knowledge. By forcing the objects of power‐ignorance into the field of perception, she occupies contradictory positions. On the one hand, she offers the potential of a transgressive performance that punctures hegemonic power, demonstrating the possibility to fashion new selves against the dominant and oppressive norm when existing in the moment and space of rupture. On the other hand, she becomes an embodied epistemological threat and the potential object of repressive violence. (R. S. P.)